Follicular fluid-derived extracellular vesicles miR-34a-5p regulates granulosa cell glycolysis in polycystic ovary syndrome by targeting LDHA - Xueying Cui; Xiaocan Lei; Tao Huang; Xueyan Mao; Zhiwei Shen; Xiuli Yang; Wanting Peng; Jingjing Yu; Shun Zhang; Peng Huo (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS) is highly prevalent in women of reproductive age worldwide, exhibits highly heterogeneous clinical presentation and biochemical parameters, and has no cure. This study aimed to investigate the role of miR-34a-5p in PCOS, its effect on glycolysis in granulosa cells (GCs), and its potential contribution to follicular dysregulation. Methods Herein, Follicular follicular fluid (FF) samples were collected from six patients with PCOS and six healthy controls undergoing in vitro fertilization-embryo transfer. The isolated extracellular vesicles were characterized by transmission electron microscopy, nanoparticle tracking analysis, and western blotting. Additionally, miRNA sequencing was performed to identify differentially expressed microRNAs, and their functions were analyzed through transcriptomics. The In vitro effects of miR-34a-5p on glycolysis, cell proliferation, and apoptosis were assessed in human ovarian granulosa tumour cell line (KGN cells). Targets of miR-34a-5p were identified by dual-luciferase reporter assays, and quantitative real-time polymerase chain reaction and western blotting were performed to determine gene and protein expression. Results The level of miR-34a-5p in FF-derived extracellular vesicles derived from patients with PCOS was significantly higher than that of the control group. Transcriptomic analysis highlighted miR-34a-5p as a key regulator of glycolysis and apoptosis. Furthermore, in vitro analysis showed that miR-34a-5p targeted lactate dehydrogenase A (LDHA), inhibited glycolysis, reduced energy supply to GCs, and promoted apoptosis of KGN cells. Conversely, miR-34a-5p inhibition restored glycolysis function and cell viability. Conclusion The findings of this study show that miR-34a-5p mediates GC apoptosis in PCOS by targeting LDHA and inhibiting glycolysis, suggesting its crucial role in PCOS pathophysiology, and offering potential therapeutic targets for improving follicular development and fertility outcomes in patients with PCOS. Further research is needed to explore the clinical implications of miR-34a-5p and its use as a biomarker for early diagnosis and prognosis of PCOS.